Roles of muthmainnah personality and alexithymia in dealing with mental health problems among university students - Dwi Yan Nugraha; Fuad Nashori; Musa Muwaga (INSPIRA: Indonesian Journal of Psychological Research, 2024)
This study inquires the roles of muthmainnah personality and alexithymia in mediating the COVID-19 exposure to mental health problems in Indonesian university students quarantined at home during COVID-19. A total of 276 students completed the following scales: Islamic Personality Scale, Toronto Alexithymia-20 Scale, and Patient Health Questionnaire-9. Then, an examination on some possible relationships of obtained data was performed by structural equation modeling and mediation analysis. This study revealed that students with muthmainnah personality had lower levels of depression. Furthermore, the muthmainnah personality could mediate COVID-19 exposure to depression experienced by the students. In addition, this study revealed that students with probable depression had more severe alexithymia, such as difficulty identifying feelings, difficulty describing feelings, and externally oriented thinking. The alexithymia could mediate COVID-19 exposure to depression. These results implied that religious aspects could be utilized as strategies to determine and overcome the students’ emotions and could significantly avoid or moderate mental health problems in the case of depression associated with COVID-19.